Tumor promoter role of miR-647 in gastric cancer via repression of TP73 - Zhang, Xiangqian (Mol Med Rep, 2018)
It has previously been demonstrated that miRNA (miR)-647 exhibits an important role in various cancers, and is aberrantly expressed in gastric cancer (GC). However, the exact role of miR-647 in GC still remains unclear. The present study aimed to investigate the functional significance of miR-647 and its target gene in GC. TargetScan and Miranda databases were used to predict the putative targets, and the prediction was validated by Dual-luciferase Reporter Assays. To investigate whether miR-647 affects GC cell behavior, a stable miR-647-overexpression/low-expression cell line was generated by transfection with miR-647 mimic/inhibitor. MTT, Flow Cytometry and Transwell invasion assays were performed to investigate the proliferation, cell apoptosis, migration and invasion properties of MGC-803 cells. Additionally, reverse transcription-quantitative polymerase chain reaction and western blot analysis were performed to detect the mRNA and protein expression levels of the apoptosis-associated genes. The results suggested that tumor protein P73 (TP73) is a target gene of miR-647. TP73 was markedly decreased following miR-647 overexpression and significantly increased following miR-647 inhibition. Following overexpression of miR-647, the proliferation, migration and invasion of MGC-803 cells were significantly increased, whereas the percentage of apoptotic cells decreased. Conversely, the proliferation, migration and invasion of MGC-803 cells were significantly declined, and the percentage of apoptotic cells increased following miR-647 inhibition. In addition, the B cell lymphoma (Bcl)-2 Associated X, Apoptosis Regulator/Bcl-2 ratio was markedly decreased when miR-647 was overexpressed by miRNA mimics, and significantly increased when miR-647 expression was inhibited via an miRNA inhibitor. Overall, miR-647 functions as a tumor promoter in GC by repressing TP73.